A cytoplasmic polyhedrosis virus in midgut cells of Anopheles stephensi and in the sporogonic stages of Plasmodium berghei yoelii - Bird, R. G. (1972)
Although it has been known for some time that nuclear and cytoplasmic polyhedrosis viruses may infect the larval stages of mosquitos capable of transmitting mammalian malaria this paper reports for the first time the presence of a cytoplasmic polyhedrosis virus in adult Anopheles stephensi. The virus was shown to be present in sporogonic stages of Plasmodium berghei yoelii with which the mosquitos were infected. It is possible that other viruses may affect both vector and malaria parasites. Further studies are required of viral infections in mosquitos as a possible method of biological control.